Transcriptomic Analysis of High- and Low-Virulence Bovine Pasteurella multocida in vitro and in vivo - He, Fang; Zhao, Zongling; Wu, Xiaoyan; Duan, Lijie; Li, Nengzhang; Fang, Rendong; Li, Pan; Peng, Yuanyi (Frontiers in Veterinary Science, 2021)
Pasteurella multocida (P. multocida) is a gram-negative opportunistic pathogen that causes various diseases in poultry, livestock and humans, resulting in huge economic losses. P. multocida serotype A CQ6 (PmCQ6) is a naturally occurring attenuated strain, while P. multocida serotype A strain CQ2 (PmCQ2) is a highly virulent strain isolated from calves. Compared with PmCQ2, it was found that bacterial loads and tissue lesions of lung tissue significantly decreased, and survival rates significantly improved in mice infected with PmCQ6 by intranasal infection. However, comparative genome analysis showed that the similarity between the two strains is more than 99%. To further explore the virulence difference mechanism of PmCQ2 and PmCQ6, transcriptome sequencing analysis of the two strains was performed. The RNA sequencing analysis of PmCQ2 and PmCQ6 showed a large number of virulence-related differentially expressed genes (DEGs) in vivo and in vitro. Among them, 38 virulence-related DGEs were significantly up-regulated due to PmCQ6 infection, while the number of that PmCQ2 infection was 46, much more than PmCQ6. In addition, there are 18 virulence-related DEGs (capsule, iron utilization, lipopolysaccharide and outer membrane protein-related genes) were up-regulated in PmCQ2 infection compared to PmCQ6 infection, exhibiting higher intensive expression level in vivo. Our findings indicate that these virulence-related DEGs might be responsible for the virulence of PmCQ2 and PmCQ6, providing prospective candidates for further studies on the pathogenesis.